Histopathological and Some Hematological Analysis in Iraqi Patients with Osteoarthritis - Nabaa S. Abdul Sahib Abdul Sahib (Journal of Global Pharma Technology, 2017)
Osteoarthritis (OA) is a biomechanical process in which the joints respond pathologically to mechanical stress, leading to articular cartilage damage and changes in other knee tissue. The present study focuses on some haematological and biochemical test in both patients and control and histopathological change with knee OA patients. Tissue samples (Synovial membrane and Cartilage) obtained from 50 knee OA patients (35 females and 15 males) during total knee replacement for histological study. Blood sample were obtained from 50 knee OA patients and 25 control. The tissue sample and blood were collected during the period from October 2015 to June 2016. In the present study, the Histological study of knee OA tissues (Synovial membrane and Cartilage) expressed many histopathological changes such as fibrin deposition, congestion blood vessels and infiltration of inflammatory cells.Assessment of differential white blood cell (WBC) level in blood revealed that both neutrophils and monocytes levels elevated significantly in total knee OA patients (male and female) in compared with that of healthy controls, but there was no significant difference in neutrophils and monocytes levels of knee OA male patients compared with that of female patients. Also, no significant difference in WBC level of knee OA patients compared with healthy control, but there was a significant difference in WBC level between male and female knee OA patients. On the other hand, no significant difference in lymphocyte level of knee OA patients compared with healthy control for both male and female. Our results showed significant elevation in erythrocyte sedimentation rate (ESR) in females as compared with males with in the patients group. Also there was significant elevation difference in ESR between total patients and controls in males and females. While, no significant difference in platelets level of female with knee OA compared with healthy, but there was highly significant elevation difference in level of platelets in knee OA male compared with control, and between knee OA female and control but there was a significant elevation in platelets level of knee OA patient male as compared with knee OA female. On the other hand, no significant difference in Hemoglobin (Hb) level between male and female knee OA patients as compared with control, and between both males and females.Keywords: Osteoarthritis, Synovial Membrane, Cartilage, Knee joint.